2022
DOI: 10.1085/jgp.202213149
|View full text |Cite
|
Sign up to set email alerts
|

Myosin essential light chain 1sa decelerates actin and thin filament gliding on β-myosin molecules

Abstract: The β-myosin heavy chain expressed in ventricular myocardium and the myosin heavy chain (MyHC) in slow-twitch skeletal Musculus soleus (M. soleus) type-I fibers are both encoded by MYH7. Thus, these myosin molecules are deemed equivalent. However, some reports suggested variations in the light chain composition between M. soleus and ventricular myosin, which could influence functional parameters, such as maximum velocity of shortening. To test for functional differences of the actin gliding velocity on immobil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…However, it is important to consider, in this connection, that other studies demonstrate a dramatic effect of essential 79,80 and regulatory 81,82 light chain isoforms on both striated muscle myosin ATPase kinetic properties and actin filament gliding velocities. Moreover, when performing experiments in parallel, Tang and coworkers 55 , observed that substitutions of the mouse regulatory chain for the human ventricular regulatory light chain (without exchange of the mouse ELC; study 3.1 vs 3.2 in Table S2) demonstrated reduced K ATPase and actin filament velocity by ~ 40% and ~ 15%, respectively (see also Fig.…”
Section: Parametersmentioning
confidence: 99%
“…However, it is important to consider, in this connection, that other studies demonstrate a dramatic effect of essential 79,80 and regulatory 81,82 light chain isoforms on both striated muscle myosin ATPase kinetic properties and actin filament gliding velocities. Moreover, when performing experiments in parallel, Tang and coworkers 55 , observed that substitutions of the mouse regulatory chain for the human ventricular regulatory light chain (without exchange of the mouse ELC; study 3.1 vs 3.2 in Table S2) demonstrated reduced K ATPase and actin filament velocity by ~ 40% and ~ 15%, respectively (see also Fig.…”
Section: Parametersmentioning
confidence: 99%